Factors Influencing the Elastic Stiffness Factor in Reinforced Concrete Structures of Dual Systems Using Pushover Analysis - Shahram Jkhsi; Saya Abdullah Saber (International Islamic University Malaysia Engineering Journal)
Stiffness is one of the most critical characteristics of a building, which is considered for public safety against earthquake loads and refers to displacement resistance. Buildings must be built with proper strength and stiffness. This study uses pushover analysis to evaluate the parameters influencing the stiffness of the RC Dual system. The research used ASCE 7-10 and ACI 318-08 codes to design 24 two-dimensional buildings. Pushover analysis is conducted in the models using the ETABS software. Factors, including the number of stories, span length, thickness of the shear walls, and compressive strength, were considered while evaluating the stiffness and base shear of the designed buildings. The highest stiffness factor is (149.30) found in low-rise buildings with smaller span lengths, higher shear wall thickness, and higher compressive strength. In comparison, the lowest stiffness factor of (27.88) appeared in high-rise buildings with longer span lengths, lower shear wall thickness, and lower compressive strength. This study analyzed a dual system consisting of a moment-resisting frame and a shear wall. In further studies, other structural systems can be considered. By increasing the span length from 5.5m to 6.5m, the stiffness factor decreases by 8%. While by increasing shear wall thickness, the stiffness factor increased by 4.5%. Since every sample consists of two-dimensional dual systems, the influence of torsion is avoided. Future work should take torsional impacts into account since they have the potential to impact the design.